ЇЗДЦІ-ІХНЕВМОНІДИ ПІДРОДИНИ ANOMALONINAE (HYMENOPTERA, ICHNEUMONIDAE) СТЕПОВОЇ ЗОНИ УКРАЇНИ - Nuzhna, A. D. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2020)
This work is the first complex research on Anomaloninae subfamily of the Ukrainian Steppe. The species of Anomaloninae are the primary larval-pupal endoparasitoids of Lepidoptera and Coleoptera. The subfamily Anomaloninae is divided into two tribes: Anomalonini with one genus Anomalon and Gravenhorstiini containing the remaining genera. Totally 62 species, belonging to 14 genera, were recorded from Ukraine. Unlike other Ichneumonidae, Anomaloninae may inhabit areas with a fairly dry climate, therefore a lot of species of this subfamily are common in the south-eastern regions of Ukraine, as well as in small steppe areas in other regions. This study is based on specimens collected in 2008 – 2016 and deposited in the collection of Schmalhausen Institute of Zoology (Kyiv). The data of 38 Anomaloninae species belonging to 10 genera from the Steppe zone of Ukraine are presented. For each species the data on material, comparative notes and distribution are given. The most widespread are these species: Anomalon cruentatum (Geoffroy, 1785), Agrypon flexorium (Thunberg, 1822), Agrypon gracilipes (Curtis, 1839), Barylypa amabilis Tosquinet, 1900, Barylypa uniguttata (Gravenhorst, 1829), Heteropelma megarthrum (Ratzeburg, 1848), Therion circumflexum (Linnaeus, 1758). Five Anomaloninae species are rare: Agrypon flexorioides Schnee, 1989, Barylypa jacobsoni (Shestakov, 1923), Erigorgus lacertosus Atanasov 1975, Habrocampulum biguttatum (Gravenhorst, 1829), Gravenhorstia picta Boie, 1836. Other species are common for the territory of Ukraine: Anomalon chinense (Kokujev, 1915), Agrypon anomelas (Gravenhorst, 1829), A. clandestinum (Gravenhorst, 1829), A. flaveolatum (Gravenhorst, 1807), A. hilare (Tosuinet, 1889), A. varitarsum (Wesmael, 1849), Aphanistes bellicosus (Wesmael, 1849), A. gliscens (Hartig, 1838), A. ruficornis (Gravenhorst, 1829), B. delictor (Thunberg, 1822), B. helleni Schnee, 1989, B. longicornis (Brauns, 1895), B. pallida (Gravenhorst, 1829), B. propugnator (Förster, 1855), B. rubricator (Szepligeti, 1899), Erigorgus cerinops (Gravenhorst, 1829), E. fibulator (Gravenhorst, 1829), E. leucopus (Förster, 1855), E. melanobatus (Gravenhorst, 1829), E. melanops (Förster, 1855), E. procerus (Gravenhorst, 1829), E. romani (Hellen, 1926), E. villosus (Gravenhorst, 1829), Therion giganteum (Gravenhorst, 1829), Trichomma enecator (Rossi, 1790), T. fulvidens Wesmael, 1849. Populations of rare Anomaloninae species should be protected in existing reserves, in addition, it is recommended to grant protection status to areas where these insects are found.